Novel Mutations in Geleophysic Dysplasia Type 1. (May 2014) - Porayette, Prashob; Fruitman, Deborah; Lauzon, Julie L.; Le Goff, Carine; Cormier-Daire, Valérie; Sanders, Stephen P.; Pinto-Rojas, Alfredo; Perez-Atayde, Antonio R.
Geleophysic dysplasia (GD) is a rare genetic disorder characterized by acromelic dysplasia. Geleophysic dysplasia type 1 (MIM 231050) is autosomal recessive and is caused by homozygous or compound heterozygous mutation in the ADAMTSL2 (a disintegrin and metalloproteinase with thrombosponding repeats-like 2) gene. Geleophysic dysplasia type 2 (MIM 614185) is autosomal dominant and is caused by heterozygous mutation in the fibrillin 1 ( FBN1 ) gene. Here, we present the clinical and histopathologic findings in a child with GD with newly identified ADAMTSL2 mutations. The 1st mutation was probably a pathogenic one, c.[1934G>A] p.[Arg645His], located in exon 13; the 2nd, in intron 8, was probably changing a splice site. While the light and electron microscopic findings were similar to those previously described, hydrocephalus due to aqueductal stenosis might be a new associated finding in these patients. This child with these 2 novel mutations also had an aggressive clinical course with early-onset progressive cardiac valvular disease.